2017
DOI: 10.1177/1369148117730542
|View full text |Cite
|
Sign up to set email alerts
|

How Brexit was made in England

Abstract: The Leave majority recorded in England was decisive in determining the UK-wide referendum result. Brexit was made in England. We take this as a prompt to challenge the conventional Anglo-British mindset that animates most studies of 'British politics', and has shaped public attitudes research on the United Kingdom. We explore the persistence of distinctive Eurosceptic views in England and their relationship to English national identity prior to the referendum. We then model referendum vote choice using data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 24 publications
4
81
1
2
Order By: Relevance
“…Three out of four devolved regions-Greater London, Northern Ireland and Scotland-voted in favour of remaining in the EU but they were dragged into Brexit against their will by England's vote. 12 Second, representatives of all devolved administrations, including Wales (where 'Leave' won), have expressed serious concerns about the possible economic implications of Brexit for their regions. Third, in the absence of well-regulated intergovernmental co-decision making, strong disagreements on the process of Brexit and on the allocation of repatriated competences across the levels of governments (Westminster versus the devolved administrations) are quickly degenerating into constitutional conflicts.…”
Section: Brexit and The Territorial Question(s)mentioning
confidence: 99%
“…Three out of four devolved regions-Greater London, Northern Ireland and Scotland-voted in favour of remaining in the EU but they were dragged into Brexit against their will by England's vote. 12 Second, representatives of all devolved administrations, including Wales (where 'Leave' won), have expressed serious concerns about the possible economic implications of Brexit for their regions. Third, in the absence of well-regulated intergovernmental co-decision making, strong disagreements on the process of Brexit and on the allocation of repatriated competences across the levels of governments (Westminster versus the devolved administrations) are quickly degenerating into constitutional conflicts.…”
Section: Brexit and The Territorial Question(s)mentioning
confidence: 99%
“…If fishermen equate and justify their Euroscepticism because leaving the EU will make them and their industry more prosperous, then we can say that it is indeed instrumental. However, if it is driven by other concerns, such as immigration, then it is likely to be more general in nature and not unlike the population as a whole (Clarke et al 2017;Goodwin and Milazzo 2017;Henderson et al 2017). It is expected that their Euroscepticism is more instrumental in nature given the direct and explicit impact that the CFP has on their everyday lives.…”
Section: Scottish Fishermen the Cfp And Brexitmentioning
confidence: 99%
“…( Hennig and Dorling : 20)Geoffrey Evans and Jonathan Mellon's research similarly revealed a wider social base that supported leaving the EU than had been assumed by politicians and academics (Evans and Mellon ). Ailsa Henderson et al went further still and argued that Brexit was essentially an English nationalist moment, suggesting too that ‘English national identity was mobilised by the Brexit question’ and concluding that ‘Brexit was made in England’ (Henderson et al : 631–32).…”
Section: Brexit and The Dilemmas Of English Nationalismmentioning
confidence: 99%